2009
DOI: 10.31610/zsr/2009.18.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Review of Kazakhstan species of the genus Pachyneuron Walker, 1833 (Hymenoptera: Chalcidoidea: Pteromalidae)

Abstract: Ten species of Pachyneuron are reported from Kazakhstan. Data on distribution and biology are reported for the first time for most of these species. A key to the species is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…It was reared from galls of various cecidomyiid species on different host plants: from stem-galls of Stefaniola iliensis Fedotova on Haloxylon persicum, from stem-galls of Stefaniola fragosa Mamaev and S. gigas (Marikovskij) on Haloxylon ammodendron, from bud-galls of Halodiplosis meridianus (Marikovskij) on the same host plant, and also from Halodiplosis nanophytonis Fedotova on Nanophyton erinaceum (Pallas) Bunge. Dzhanokmen (2005) also reported adults of this pteromalid species collected on blooming Tamarix spp. (Tamaricaceae).…”
Section: Mesopolobus Westwood 1833mentioning
confidence: 85%
See 4 more Smart Citations
“…It was reared from galls of various cecidomyiid species on different host plants: from stem-galls of Stefaniola iliensis Fedotova on Haloxylon persicum, from stem-galls of Stefaniola fragosa Mamaev and S. gigas (Marikovskij) on Haloxylon ammodendron, from bud-galls of Halodiplosis meridianus (Marikovskij) on the same host plant, and also from Halodiplosis nanophytonis Fedotova on Nanophyton erinaceum (Pallas) Bunge. Dzhanokmen (2005) also reported adults of this pteromalid species collected on blooming Tamarix spp. (Tamaricaceae).…”
Section: Mesopolobus Westwood 1833mentioning
confidence: 85%
“…on Haloxylon spp. However, Dzhanokmen (2005) reported that this species was reared in Kazakhstan from Halodiplosis vernalis (Marikovskij), as well as from H. saxauli Kaplin and Baldratia kozlovi Marikovskij on H. persicum. At the same site in Fukang we also collected M. deserti by sweeping on Tamarix sp., which is a new host plant record for this pteromalid species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations